Multisystem Inflammatory Syndrome in Children and Long COVID: The SARS-CoV-2 Viral Superantigen Hypothesis - Noval Rivas, Magali; Porritt, Rebecca A.; Cheng, Mary Hongying; Bahar, Ivet; Arditi, Moshe (Frontiers in Immunology, 2022)
Multisystem inflammatory syndrome in children (MIS-C) is a febrile pediatric inflammatory disease that may develop weeks after initial SARS-CoV-2 infection or exposure. MIS-C involves systemic hyperinflammation and multiorgan involvement, including severe cardiovascular, gastrointestinal (GI) and neurological symptoms. Some clinical attributes of MIS-C—such as persistent fever, rashes, conjunctivitis and oral mucosa changes (red fissured lips and strawberry tongue)—overlap with features of Kawasaki disease (KD). In addition, MIS-C shares striking clinical similarities with toxic shock syndrome (TSS), which is triggered by bacterial superantigens (SAgs). The remarkable similarities between MIS-C and TSS prompted a search for SAg-like structures in the SARS-CoV-2 virus and the discovery of a unique SAg-like motif highly similar to a Staphylococcal enterotoxin B (SEB) fragment in the SARS-CoV-2 spike 1 (S1) glycoprotein. Computational studies suggest that the SAg-like motif has a high affinity for binding T-cell receptors (TCRs) and MHC Class II proteins. Immunosequencing of peripheral blood samples from MIS-C patients revealed a profound expansion of TCR β variable gene 11-2 (TRBV11-2), which correlates with MIS-C severity and serum cytokine levels, consistent with a SAg-triggered immune response. Computational sequence analysis of SARS-CoV-2 spike further identified conserved neurotoxin-like motifs which may alter neuronal cell function and contribute to neurological symptoms in COVID-19 and MIS-C patients. Additionally, autoantibodies are detected during MIS-C, which may indicate development of post-SARS-CoV-2 autoreactive and autoimmune responses. Finally, prolonged persistence of SARS-CoV-2 RNA in the gut, increased gut permeability and elevated levels circulating of S1 have been observed in children with MIS-C. Accordingly, we hypothesize that continuous and prolonged exposure to the viral SAg-like and neurotoxin-like motifs in SARS-CoV-2 spike may promote autoimmunity leading to the development of post-acute COVID-19 syndromes, including MIS-C and long COVID, as well as the neurological complications resulting from SARS-CoV-2 infection.